2000
DOI: 10.1046/j.1365-2273.2000.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of beta-actin as a candidate autoantigen in autoimmune inner ear disease

Abstract: It has been shown that sera from patients with autoimmune inner ear disease contain antibodies to several inner ear antigens. We report here the characterization of the 42-43 kDa protein against which a significant number of patients' sera react strongly. After separation of inner ear proteins from guinea-pig cochleas by SDS-PAGE, the band corresponding to the 42-43 kDa protein was digested with trypsin and the peptide fragments were separated by high-performance liquid chromatography. Two fractions were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 35 publications
0
26
0
2
Order By: Relevance
“…Such antibodies have also been proposed as being responsible for so-called autoimmune inner ear disease. A number of putative inner ear antigens have been proposed as targets of such antibodies, including type 2 collagen [66] , ␤ -actin [67] , cochlin [68,69] , and ␤ -tectorin [69] . The best documented of these candidate antibodies is to choline transporter-like protein 2 (CTL2) [70] .…”
Section: Immunologic Theorymentioning
confidence: 99%
“…Such antibodies have also been proposed as being responsible for so-called autoimmune inner ear disease. A number of putative inner ear antigens have been proposed as targets of such antibodies, including type 2 collagen [66] , ␤ -actin [67] , cochlin [68,69] , and ␤ -tectorin [69] . The best documented of these candidate antibodies is to choline transporter-like protein 2 (CTL2) [70] .…”
Section: Immunologic Theorymentioning
confidence: 99%
“…This work has direct clinical application to perilymphatic fistulas. Several other laboratories have used 2D-gels to investigate inner ear autoimmune diseases (Billings et al, 1995;Boulassel et al, 2000;Harris et al, 1990), otoconia (Cao et al, 1996), glucocorticoid regulated inner ear gene expression (Yao et al, 1995), otosclerosis (Ribari et al, 1983), expression of chloride transport systems in auditory brainstem (Nothwang et al, 2003), analysis of the Coch gene (Ikezono et al, 2001), and calcium binding proteins of the cochlea (Winsky et al, 1989a,b).…”
Section: Advances In Proteomics Of the Inner Earmentioning
confidence: 99%
“…In bovine ear experiments, Ikezono et al demonstrated that the protein product of the Coch gene, which underlies the human deafness syndrome DFNA9 (Robertson et al, 1998), is abundant in the ear (Ikezono et al, 2004). 2DE has been applied in several other studies but with varying success (Boulassel et al, 2000). Other studies include localizations of individual proteins and functional determinations (Royaux et al, 2003), as well as correlation of expression of the actin filamentbundling protein espin with stereociliary bundle formation in the developing ear .…”
Section: Current Stage Of Proteomics In Auditory Developmental and DImentioning
confidence: 99%